Anaplastic Lymphoma Kinase Is a Regulator of Alcohol Consumption and Excitatory Synaptic Plasticity in the Nucleus Accumbens Shell - Mangieri, Regina A.; Maier, Esther Y.; Buske, Tavanna R.; Lasek, Amy W.; Morrisett, Richard A. (Frontiers in Pharmacology, 2017)
Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase recently implicated in biochemical, physiological, and behavioral responses to ethanol. Thus, manipulation of ALK signaling may represent a novel approach to treating alcohol use disorder (AUD). Ethanol induces adaptations in glutamatergic synapses onto nucleus accumbens shell (NAcSh) medium spiny neurons (MSNs), and putative targets for treating AUD may be validated for further development by assessing how their manipulation modulates accumbal glutamatergic synaptic transmission and plasticity. Here we report that Alk knockout (AlkKO) mice consumed greater doses of ethanol, relative to wild-type (AlkWT) mice, in an operant self-administration model. Using ex vivo electrophysiology to examine excitatory synaptic transmission and plasticity at NAcSh medium spiny neurons that express dopamine D1 receptors (D1MSNs), we found that the amplitude of spontaneous excitatory postsynaptic currents (EPSCs) in NAcSh D1MSNs was elevated in AlkKO mice and in the presence of an ALK inhibitor, TAE684. Furthermore, when ALK was absent or inhibited, glutamatergic synaptic plasticity – long term depression (LTD) of evoked EPSCs – in D1MSNs was attenuated. Thus, loss of ALK activity in mice is associated with elevated ethanol consumption and enhanced excitatory transmission in NAcSh D1MSNs. These findings add to the mounting evidence of a relationship between excitatory synaptic transmission onto NAcSh D1MSNs and ethanol consumption, point toward ALK as one important molecular mediator of this interaction, and further validate ALK as a target for therapeutic intervention in the treatment of AUD.